2019
DOI: 10.1002/ece3.5449
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of rainforest to oil palm and rubber plantations alters energy channels in soil food webs

Abstract: In the last decades, lowland tropical rainforest has been converted in large into plantation systems. Despite the evident changes above ground, the effect of rainforest conversion on the channeling of energy in soil food webs was not studied. Here, we investigated community‐level neutral lipid fatty acid profiles in dominant soil fauna to track energy channels in rainforest, rubber, and oil palm plantations in Sumatra, Indonesia. Abundant macrofauna including Araneae, Chilopoda, and Diplopoda contained high am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 111 publications
(186 reference statements)
1
23
4
Order By: Relevance
“…These findings are in line with the results of the study of Krause et al (2019) investigating oribatid mites at the same study sites and showing that the shift in trophic niches to be mainly due to changes in the use of basal resources rather than trophic levels. Similar to previous studies on centipedes, oribatid mites and other soil animal taxa ( Klarner et al, 2017 ; Susanti et al, 2019 ; Krause et al, 2019 ), we also found the conversion of rainforest into plantations to be associated in Collembola with a shift from detritivory towards herbivory (i.e., lower 13 C enrichment). In rainforest and jungle rubber, δ 13 C values of Collembola were 2.0–5.0‰ higher compared to leaf litter, which resembles the shift observed in temperate forest ecosystems ( Pollierer et al, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are in line with the results of the study of Krause et al (2019) investigating oribatid mites at the same study sites and showing that the shift in trophic niches to be mainly due to changes in the use of basal resources rather than trophic levels. Similar to previous studies on centipedes, oribatid mites and other soil animal taxa ( Klarner et al, 2017 ; Susanti et al, 2019 ; Krause et al, 2019 ), we also found the conversion of rainforest into plantations to be associated in Collembola with a shift from detritivory towards herbivory (i.e., lower 13 C enrichment). In rainforest and jungle rubber, δ 13 C values of Collembola were 2.0–5.0‰ higher compared to leaf litter, which resembles the shift observed in temperate forest ecosystems ( Pollierer et al, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…We attributed low δ 15 N values in epedaphic and atmobiotic Collembola to algae or lichen feeding, which is widespread in Collembola in temperate forests ( Potapov Korotkevich & Tiunov, 2018 ), but in our study only few species had δ 15 N values below those of litter. This contradicts results based on fatty acid analysis suggesting that Collembola feed more on algae in tropical than in temperate ecosystems ( Susanti et al, 2019 ). To clarify the contribution of algae in soil food webs in tropical and temperate ecosystems, more data on stable isotope composition of various food resources in tropical forests, or direct experimentation, are needed.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…They are linked to energy channels originating directly from plants or from bacteria and fungi utilizing plant‐derived resources (Moore and Hunt 1988, Moore et al 2005). The relative importance of these different energy channels may shift with land‐use intensity (Moore 1994, Bardgett et al 1996, de Vries et al 2013, Susanti et al 2019), ecosystem type (e.g., forests vs. grasslands; Crotty et al 2014), forest type (Ferlian and Scheu 2014), or even tree species/leaf litter type (Wardle et al 2006, D’Annibale et al 2017). In addition, local abiotic factors also influence the relative importance of these energy channels for soil food webs (Ferlian et al 2012).…”
Section: Introductionmentioning
confidence: 99%